Experimental measurement and numerical simulation of the thermal performance of a double glazing system with an interstitial Venetian blind. (July 2016) - Sun, Yanyi; Wu, Yupeng; Wilson, Robin; Lu, Sixu
Abstract: Venetian blinds, which were originally designed to provide sun shading and privacy, also have the potential to reduce heat transfer caused by internal and external temperature difference when integrated within the cavity between the two panes of a double glazing unit. In this paper, the thermal performance of a glazing system with and without a Venetian blind with various slat orientation angles under different temperature conditions is investigated through both experiment (undertaken in a large climate chamber) and numerical simulation (obtained via Computational Fluid Dynamic modelling). The thermal resistance of a Venetian blind glazing system varies with the change of slat inclination angle, and it also highly depends on the mean temperature of the glazing and the temperature difference between the indoor and outdoor environment. Inclusion of a Venetian blind modifies both the absolute and relative strengths of convection and radiation. Vertically oriented slats showed the most significant contribution to increasing radiative thermal resistance, which led to the best overall thermal performance. The system achieved up to 28% improvement of U-value when compared with a glazing unit without a Venetian blind. Empirical correlations generated based on simulations could be used for future building energy simulation. Highlights: Thermal performance of double glazing with interstitial Venetian blind was experimentally and numerically investigated. The convection and radiation of the systems were detailed analysed. Thermal resistances under various mean temperatures and temperature differences of two glazing panes were investigated. The slats orientation significantly affects the thermal performance of the system. Empirical correlation to calculate thermal resistance of the system at different slat orientation angles is proposed.